Sustainable Development and Nature: The Social and The Material. (17th April 2013) - Redclift, Michael; Woodgate, Graham; Springett, Delyse
ABSTRACT In this paper we argue that one way of viewing the relationship between sustainable development and nature is to explore the extent to which human‐made capital can be substituted for nature ('natural capital'). It is suggested that this substitution/replacement exposes societies to different risks and uncertainties. Our point of departure is to distinguish sociologically between different 'natures', which reflect different levels of human/natural capital substitution and degrees of hybridity: First Nature, Second Nature, Third Nature and Fourth Nature. This approach to sustainable development – through investigating the co‐existence of human‐made and natural capital, and the effects of this process on risk and uncertainty – is used to explain the vicissitudes of much of the 'sustainable development' debate. Focusing on sustainable consumption and ecological modernization, the paper also suggests that regulation theory might help to explain how different environmental policy options are chosen, and the limitations of these options. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment.